Multiple Medullary Schwannoma Associated with Lumbar Disc Herniation and Cauda Equina Syndrome: Case Report - Rodrigues Neto, Anibal; Bicalho, Bianca; Varandas, Giovanna Maria; Antonucci, Adriano Torres; Castro, Gabriel Gomes Freitas de; Arruda, Shiro Manoel Shimoakoishi de; Schiavini, Marcel; Santos, Lutero Cleuler Moraes dos; Lehmann, Márcio Francisco; Pesente, Francisco Spessatto (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Introduction Schwannoma is a Schwann cells neoplasm that can occur in various parts of the nervous system, including the medullar region of the cauda equina. Bone involvement is uncommon.Objective To report a multiple schwannoma case that was initially diagnosed as cauda equina syndrome.Clinical Case We report the case of a 44-year-old male who presented with pain irradiating to the lower limbs, urinary retention, and saddle paresthesia. Imaging exams revealed tumors in the cervical spine and in the T12/L1, L2/L3, and L3/L4 levels, the last three causing nervous compression. Histopathological analyses confirmed a Schwannoma pattern.Results The case was solved by surgical resection.Conclusion The case was solved and, in the end, the patient was stable and with improved pain and waits for a cervical surgery.
Keywords: schwannoma; neoplasm; lumbalgia